Lithium-ion battery positive electrode additive, positive electrode plate and lithium-ion battery
By using LixAyC2O4 doped ion A as the positive electrode additive in lithium-ion batteries, the deliquency potential is reduced, and the problem of lithium ion consumption during the first charging and discharging of lithium-ion batteries is solved, thereby improving battery capacity and stability.
Patent Information
- Application Number
- CN202111680874.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-12-30
AI Technical Summary
Existing lithium-ion batteries consume lithium ions due to the formation of the SEI film during the first charging and discharging, resulting in a decrease in battery capacity and energy density. The deliquency potential of the commonly used lithium-enhancing material Li2C2O4 is too high, limiting its application range.
LixAyC2O4 with doped ions A (such as K+ and Na+) is used as the positive electrode additive, and lattice distortion is introduced through A ions with large ion radius, reducing the force between Li+ and anion, making Li+ easier to decompose at lower voltages. , lithium supplementation is provided, and the radius of A is greater than Li+, so that the deliquification potential is reduced to below 4.6V.
It realizes effective decomposition and release of active lithium at low voltage, supplements the lithium ion consumption of the negative electrode SEI film, improves the capacity and stability of the battery, and avoids irreversible changes in the material structure at high voltage.
Smart Images

Figure CN116417611B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a lithium ion battery positive electrode additive material, a positive electrode plate and a lithium ion battery. Background Art
[0002] When a lithium-ion battery is charged and discharged for the first time, the solid-liquid interface between the electrode and the electrolyte will react to form a "passivation film", namely the SEI film, on the surface of the electrode material. The formation of the SEI film will consume some lithium ions, increase the irreversible capacity of the first charge and discharge of the lithium-ion battery, and reduce the charge and discharge efficiency. Therefore, it is necessary to supplement lithium to the electrode material to offset the lithium ion consumption caused by the formation of the SEI film and increase the capacity and energy density of the battery.
[0003] In the literature "Sophie Solchenbach et al. Lithium Oxalate as Capacity and Cycle-Life Enhancer in LNMO / Graphite and LNMO / SiG Full Cells. Journal of The Electrochemical Society, 165(3): A512-A524", it is reported that Li2C2O4 material decomposes and releases lithium at around 4.7V. The Li + It can migrate to the negative electrode and replenish the active lithium consumed by the formation of the negative electrode SEI film. Li2C2O4 material can be used as a lithium supplement material. However, the literature report shows that the potential (lithium removal potential) of Li2C2O4 decomposition and release of lithium ions is as high as 4.7V, which is only applicable to high-voltage lithium-ion battery systems, such as LiNi 0.5 Mn 1.5 O2 (working voltage 4.7-4.8V), while for most positive electrode materials, the delithiation potential value is much higher than its charging cut-off voltage, especially for ternary materials. The higher the charging voltage, the greater the irreversible change in its structure, which seriously affects its structural stability and cycle performance. The delithiation potential of Li2C2O4 limits its application as a lithium supplement material. Summary of the invention
[0004] The object of the present invention is to provide a lithium ion battery positive electrode additive with a lower decomposition and delithiation potential, a positive electrode plate containing the additive material, and a lithium ion battery.
[0005] The first aspect of the present invention provides a positive electrode additive for a lithium ion battery. The positive electrode additive for a lithium ion battery is Li x A y C2O4, A is selected from K + and Na +At least one of the following, x+y=2, 1<x<2.
[0006] The additive material Li of the present invention x A y In C2O4, the cation Li + is +1, and the valence state of the doped cation A is the same as that of Li + The same is +1, the difference is the ionic radius: A + (Na + Radius 97pm, K + The radius of the ion is 133 pm, which is larger than that of Li + (Li + Radius 68pm) ion radius, doping ion A + Radius Li x A y The mechanism of the influence of C2O4 delithiation potential is: doping A + Substituting part of Li in Li2C2O4, the large radius A + Ions cause lattice distortion, increasing the lattice interlayer spacing, which in turn leads to Li + The distance between the anion and the anion increases, and the interaction between the two weakens, so during the charging process, Li x A y Li in C2O4 + It is easier to decompose and release active lithium, Li x A y C2O4 has a low decomposition and delithiation potential.
[0007] The lithium-ion battery positive electrode additive of the present invention can decompose and release active lithium at a relatively low voltage (i.e., has a relatively low delithiation potential), reducing the delithiation potential to below 4.6V, and realizing the release of active lithium at a low potential. The active lithium released by the additive is used to supplement the consumption of lithium by the negative electrode SEI film. The low delithiation potential avoids the irreversible destruction of various material structures in the battery under high voltage, thereby improving the battery's electrochemical properties such as capacity and stability. The above-mentioned delithiation potential refers to the decomposition of the lithium-ion battery positive electrode additive, Li + The potential of releasing active lithium.
[0008] In some implementations of the present invention, the value range of x is 1.5≤x<2; preferably 1.9≤x<2.
[0009] In some embodiments of the present invention, the above-mentioned Li x A y The delithiation potential of C2O4 is not higher than 4.6V; preferably, the Li x A y The delithiation potential of C2O4 is 4.1V~4.6V.
[0010] In some embodiments of the present invention, the above-mentioned Li x A y The average particle size of C2O4 is 50nm~10μm, preferably 100nm~1μm.
[0011] The second aspect of the present invention provides a lithium ion battery positive electrode plate, comprising a positive electrode active material and the lithium ion battery positive electrode additive provided by the first aspect of the present invention.
[0012] In some embodiments of the present invention, the above-mentioned lithium ion battery positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer satisfies the following conditions (1) or (2):
[0013] (1) The positive electrode material layer comprises a lithium ion battery positive electrode additive and a positive electrode active material mixed together;
[0014] (2) The positive electrode material layer includes a positive electrode active material layer and a positive electrode additive material layer provided on the positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode additive material layer includes a lithium ion battery positive electrode additive.
[0015] Specifically, the "positive electrode material layer", "positive electrode active material layer" and "positive electrode additive material layer" may contain, in addition to the lithium-ion battery positive electrode additives and / or positive electrode active materials mentioned above, materials required for forming pole pieces, such as conductive agents and binders, etc. The conductive agents and binders may be selected from the conductive agents and binders commonly used in the art, which will not be described in detail here.
[0016] The positive electrode active material is selected from at least one of LiFePO4, LiMn2O4 and nickel-cobalt-manganese ternary material (NCM). In the lithium-ion battery positive electrode plate, the mass ratio r of the lithium-ion battery positive electrode additive to the positive electrode active material satisfies 0<r≤0.15.
[0017] A third aspect of the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode sheet provided by the second aspect of the present invention.
[0018] The technical solution of the present invention has the following beneficial effects:
[0019] (1) The positive electrode additive of the lithium ion battery of the present invention decomposes to produce active lithium and gas, thereby replenishing lithium. Charging the battery in a suitable charge and discharge range can make the positive electrode additive material Li x A y C2O4 decomposes, and the decomposition product is active lithium Li + and gaseous carbon dioxide CO2. + Used to replenish the active lithium consumed by SEI and increase battery capacity.
[0020] (2) The lithium ion battery positive electrode additive of the present invention has a low lithium desorption potential and a high lithium desorption specific capacity. x A y Due to the introduction of doping atoms A in the C2O4 structure, the lattice distortion caused by the large ion radius of A increases the interlayer spacing, weakening the interaction between Li and anions, making it easier for Li to be released during charging, and having a low delithiation potential. The material is used as a positive electrode additive to achieve decomposition and delithiation under relatively low voltage conditions. The additive is suitable for positive electrode material systems such as LiFePO4, LiMn2O4, and NCM, and decomposes at a low voltage of 4.1-4.6V to complete the lithium replenishment of the negative electrode, avoiding the irreversible structural changes of the positive electrode active material under continuous high charging voltage conditions, thereby improving the stability and cycle performance of the battery.
[0021] Other features and advantages of the technical solution of the present invention will be described in detail in the specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the charge and discharge curve of battery samples S3, S4, S5 and DS1 at a charge and discharge rate of 0.1C;
[0023] Figure 2 It is the charge and discharge curve of battery samples S4 and S6 at a charge and discharge rate of 0.1C. DETAILED DESCRIPTION
[0024] The first aspect of the present invention provides a positive electrode additive for a lithium ion battery. The positive electrode additive for a lithium ion battery is Li x A y C2O4, A is K + and Na + At least one of the following, x+y=2, 1<x<2.
[0025] The lithium ion battery positive electrode additive Li x A y In C2O4, A ion is K + 、Na + or K + and Na + The combination of Na + Radius 97pm, K + The radius is 133 pm, Li + The radius of Li is 68 pm. Different doping A ions have different effects on the lattice interlayer spacing. The larger the A ion radius, the smaller the Li x A y The larger the C2O4 lattice interlayer spacing, the +The weaker the adsorption between the anion and the anion, the lower the delithiation potential. The A ion and Li have the same +1 valence. The larger the radius of the A ion, the lower the delithiation potential. x A y The larger the interlayer spacing of the C2O4 lattice, the weaker the interaction between Li and O in the same lattice.
[0026] Li x A y In C2O4 material, the proportion y of A and the proportion x of Li must satisfy the principle of electrical neutrality, that is, x+y=2.
[0027] Li x A y In C2O4 materials, the role of A ions is to weaken the interaction between Li ions and anions in the same lattice, reduce the delithiation potential of the material, and do not participate in providing active lithium ions to the negative electrode. x A y The delithiation potential of C2O4 material decreases, which means that Li x A y When C2O4 is used as a cathode additive, it can decompose and release active lithium at a lower voltage, which is more compatible with the charging cut-off voltage of conventional batteries, but it will cause Li x A y The available active lithium content of C2O4 is reduced, and the lithium supplement capacity is low. Therefore, the proportion x of Li should not be too low. A is used as an additive material Li x A y The proportion of A in C2O4 doping ions should not be too high. When x = 2, Li x A y The C2O4 material does not contain A. At this time, the proportion of Li is high, and the theoretical mass specific capacity is 526mAh / g. However, the lack of cation A will affect the lattice interlayer spacing, which will lead to a high delithiation potential of the material and poor compatibility with the charging cut-off voltage of conventional batteries. Therefore, the proportion of Li x should not be too high. Considering the delithiation potential and lithium replenishment capacity of the additive material, x is 1<x<2. Within this range, A with a large ionic radius makes Li x A y The effect of the increased interlayer spacing of the C2O4 lattice is sufficient to ensure the preferential release of Li, making the additive material Li x A y The decomposition potential of C2O4 is no higher than 4.6V, which will not affect the positive electrode active material, electrolyte and other battery components, while ensuring that Li x A y The C2O4 material has a high specific capacity for replenishing lithium, and can provide more active lithium to compensate for the active lithium consumed by the negative electrode SEI, without affecting its lithium replenishment effect as a positive electrode additive. Preferably, 1.5≤x<2, and more preferably, 1.9≤x<2.
[0028] The above Li x A y The delithiation potential of C2O4 is not higher than 4.6V; preferably, the above Li x A y The delithiation potential of C2O4 is 4.1V to 4.6V. This delithiation potential can be achieved by ensuring that Li x A y C2O4 has a higher specific capacity for lithium replenishment, providing more active lithium to make up for the active lithium consumed by the negative electrode SEI, while not affecting the positive electrode active material, electrolyte and other battery components.
[0029] Li x A y As an additive material that can provide active lithium ions, C2O4 has a large A ion radius that increases the lattice interlayer spacing, weakening the interaction between anions and Li, which is beneficial to Li x A y In addition to the decomposition of C2O4, good conductivity must be ensured during the charging process. x A y The conductivity of C2O4 itself is poor, so it needs to be in full contact with the conductive agent to improve its conductivity. x A y When the particle size of C2O4 is too large, the Li x A y C2O4 accounts for Li x A y The low proportion of total C2O4 will slow down its decomposition rate and may cause the delithiation potential to rise. When the polarization reaches the cut-off voltage, Li x A y The decomposition of C2O4 is incomplete, Li x A y The active lithium in C2O4 cannot be fully released to maximize the lithium supplementation effect; when Li x A y When the particle size of C2O4 is small, Li x A y C2O4 is in full contact with the conductive agent, which is beneficial to Li x A y Decomposition of C2O4, but processing of smaller particle size Li x A y The process of C2O4 is difficult, and the smaller particle size of Li x A y C2O4 is prone to secondary aggregation, poor stability in the air, and easy to absorb water. x A yC2O4 material decomposition lithium supplement performance and physical and chemical properties, Li x A y The particle size of C2O4 is preferably 50 nm to 10 μm, more preferably 100 nm to 1 μm.
[0030] A second aspect of the present invention provides a lithium ion battery positive electrode plate, comprising the lithium ion battery positive electrode additive provided by the first aspect of the present invention.
[0031] In the present invention, the positive electrode plate of the lithium-ion battery comprises a positive electrode current collector and a positive electrode material layer arranged on the positive electrode current collector; x A y As an additive material, C2O4 is introduced into the positive electrode material layer in a manner including but not limited to direct mixing and coating. x A y C2O4 is directly mixed with positive electrode active materials, conductive agents, binders, etc., and slurry coating is performed to obtain a positive electrode additive material Li x A y C2O4 positive electrode material layer, at this time, the positive electrode material layer contains a mixed lithium ion battery positive electrode additive, positive electrode active material, conductive agent and binder; coating method, that is, Li x A y C2O4 is mixed with a conductive agent and a binder, and slurried and coated on a positive electrode active material layer comprising a positive electrode active material, a conductive agent and a binder to obtain a multilayer positive electrode material layer containing a positive electrode additive material layer. At this time, the positive electrode material layer comprises a positive electrode active material layer and a positive electrode additive material layer arranged on the positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode additive material layer comprises a lithium ion battery positive electrode additive, a conductive agent and a binder; in some embodiments of the present invention, the above-mentioned positive electrode additive material layer may also include a positive electrode active material, that is, the positive electrode additive material layer comprises a lithium ion battery positive electrode additive, a positive electrode active material, a conductive agent and a binder.
[0032] When Li x A y When C2O4 is used as a positive electrode additive material to replenish lithium to the negative electrode, the Li2O4 can be set according to the maximum charge cut-off voltage that the battery system can withstand, taking into account the lithium removal potential and lithium removal specific capacity. x A y The doping amount of A cations in C2O4 and Li x A yThe amount of C2O4 added can obtain the maximum lithium replenishment capacity without affecting the battery system. For example, the positive electrode of a lithium-ion battery includes a positive electrode active material, the types of positive electrode active materials include but are not limited to LiFePO4, LiMn2O4 and NCM ternary materials, and the positive electrode active material can be selected from at least one of LiFePO4, LiMn2O4 and nickel-cobalt-manganese ternary materials. Specifically, the chemical formula of the NCM ternary material is LiNi a Co b Mn 1-a-b O2, where 0<a<1, 0<b<1.
[0033] The irreversible capacity loss in the reference battery system accounts for 0-20%. To compensate for this part of the lost capacity, the delithiation capacity contributed by the positive electrode additive should be approximately equal to the loss value. Taking into account the delithiation specific capacity of the positive electrode additive and the specific capacity of the positive electrode active material, the ratio r of the mass of the positive electrode additive to the mass of the positive electrode active material in the lithium-ion battery positive electrode sheet can be in the range of 0<r≤0.15.
[0034] Among them, binder and conductive agent are conventional choices in the field of batteries. For example, the binder can be selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin (such as polyethylene, polypropylene, polystyrene), sodium carboxymethyl cellulose (CMC), sodium alginate, etc., but not limited thereto. The conductive agent can be at least one of carbon black (such as acetylene black, Ketjen black), carbon nanotubes (CNT), graphene, carbon fiber, graphite, etc., but not limited thereto. In addition, the positive electrode current collector may include but is not limited to metal film materials, foam metal mesh, etc., and may specifically be aluminum foil, carbon-coated aluminum foil, etc.
[0035] In a third aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode sheet provided in the second aspect of the present invention.
[0036] In addition to the lithium-ion battery positive electrode sheet provided by the second aspect of the present invention, the lithium-ion battery disclosed in the present invention may also include a negative electrode sheet, a separator and an electrolyte.
[0037] In the present application, the negative electrode plate is a conventional choice in the field of batteries. The diaphragm is used to separate the positive electrode plate and the negative electrode plate to maintain the insulation between the two; the diaphragm, the positive electrode plate and the negative electrode plate together constitute the battery cell, and the battery cell is accommodated in the battery shell, and the battery shell can be an aluminum-plastic film. The diaphragm can be a polymer diaphragm, a non-woven fabric and other commonly used battery diaphragms, including but not limited to single-layer PP (polypropylene) film, single-layer PE (polyethylene) film, double-layer PP / PE, double-layer PP / PP and three-layer PP / PE / PP. The battery shell is injected with an electrolyte, which is a medium for the transmission of lithium ions between the positive and negative electrode plates. The specific composition of the electrolyte is a conventional choice in the field of batteries and is not limited to this.
[0038] The preparation method of the above-mentioned lithium-ion battery includes: stacking the positive electrode plate, the separator and the negative electrode plate in sequence to form a battery cell, accommodating the battery cell in a battery shell, injecting an electrolyte, and then sealing the battery shell to obtain a lithium-ion battery.
[0039] The present invention will be further described in detail below through embodiments in conjunction with the accompanying drawings.
[0040] Example 1
[0041] The average particle size of Li is 300 nm. 1.05 K 0.95 C2O4 is the positive electrode material, acetylene black is the conductive agent, polyvinylidene fluoride (PVDF) is the binder, and N-methylpyrrolidone (NMP) is the dispersant. After being mixed evenly in a mass ratio of positive electrode: acetylene black: PVDF: NMP = 85:10:5:50, aluminum foil is used as the current collector for coating, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and cut into pieces to make positive electrode sheets. Metal lithium sheet is used as negative electrode, celgard2400 polypropylene porous membrane is used as separator, and a mixed solution of 1mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (the volume ratio of EC and DMC is = 1:1) is used as electrolyte; the test battery is assembled in a glove box filled with argon to obtain battery sample S1.
[0042] Example 2
[0043] The battery sample S2 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.5 K 0.5 C2O4.
[0044] Example 3
[0045] The battery sample S3 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.9 K0.1 C2O4.
[0046] Example 4
[0047] The battery sample S4 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 K 0.06 C2O4.
[0048] Example 5
[0049] The battery sample S5 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.98 K 0.02 C2O4.
[0050] Example 6
[0051] The battery sample S6 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 Na 0.06 C2O4.
[0052] Example 7
[0053] The battery sample S7 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 300 nm. 1.94 K 0.03 Na 0.03 C2O4.
[0054] Example 8
[0055] The battery sample S8 was prepared by referring to the method in Example 1, except that the positive electrode material used was Li with an average particle size of 1 μm. 1.94 K 0.06 C2O4.
[0056] Example 9
[0057] The positive electrode sheet was prepared by referring to the method in Example 1, except that the positive electrode materials used were LiFePO4 and Li 1.0s K 0.95C2O4 (300nm). Graphite was used as the negative electrode material, styrene-butadiene rubber (SBR) as the binder, sodium carboxymethyl cellulose (CMC) as the thickener, and water (H2O) as the dispersant. The mixture was evenly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50, and then coated on the copper foil. The mixture was then placed in a 90°C oven for drying for 24 hours, and then pressed and cut into negative electrode sheets. Celgard 2400 polypropylene porous membrane was used as the diaphragm, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) was used as the electrolyte. The test battery was assembled in a glove box filled with argon to obtain the battery sample S9.
[0058] Example 10
[0059] The battery sample S10 was prepared by referring to the method in Example 9, except that the positive electrode materials used were LiFePO4 and Li 1.5 K 0.5 C2O4.
[0060] Embodiment 11
[0061] The battery sample S11 was prepared by referring to the method in Example 9, except that the positive electrode materials used were LiFePO4 and Li 1.94 K 0.06 C2O4.
[0062] Example 12
[0063] The battery sample S10 was prepared by referring to the method in Example 9, except that the positive electrode materials used were LiFePO4 and Li 1.94 K 0.03 Na 0.03 C2O4.
[0064] Embodiment 13
[0065] (1) LiFePO4 was used as a positive electrode active material, acetylene black was used as a conductive agent, polyvinylidene fluoride (PVDF) was used as a binder, and N-methylpyrrolidone (NMP) was used as a dispersant. The mixture was uniformly mixed in a mass ratio of positive electrode active material: acetylene black: PVDF: NMP = 85:10:5:50, and then coated with aluminum foil as a positive electrode current collector. The mixture was then placed in an oven at 120°C and vacuum dried for 24 hours to obtain a positive electrode active material layer.
[0066] (2) According to the mass ratio of Li 1.94 K 0.06C2O4 (average particle size of 300 μm): acetylene black: PVDF: NMP = 85:10:5:50 are mixed evenly to obtain a mixed slurry, which is then coated on the positive electrode active material layer obtained in step (1), and then placed in a 120°C oven for vacuum drying for 24 hours, and then pressed and cut into sheets to form a composite positive electrode sheet. In the positive electrode sheet, LiFePO4 and Li 1.94 K 0.06 The mass ratio of C2O4 is 90:10.
[0067] (3) Graphite is used as the negative electrode material, styrene-butadiene rubber (SBR) is used as the binder, sodium carboxymethyl cellulose (CMC) is used as the thickener, and water (H2O) is used as the dispersant. The mixture is uniformly mixed in a mass ratio of graphite: SBR: CMC: H2O = 100: 3: 2: 50, and then coated on a copper foil, and then placed in a 90°C oven for drying for 24 hours, and then pressed and cut into pieces to form a negative electrode. The composite positive electrode obtained in step (2) is used as the positive electrode, Celgard 2400 polypropylene porous membrane is used as the separator, and a mixed solution of 1 mol / L LiPF6 of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio = 1: 1) is used as the electrolyte; the test battery is assembled in a glove box filled with argon to obtain a battery sample S13.
[0068] Comparative Example 1
[0069] The battery sample DS1 was manufactured by referring to the method in Example 1, except that the positive electrode material used was Li2C2O4.
[0070] Comparative Example 2
[0071] The battery sample DS2 was manufactured by referring to the method in Example 9, except that the positive electrode material used was LiFePO4.
[0072] Elemental quantitative analysis
[0073] According to EPA6010D-2018D inductively coupled plasma atomic emission spectrometry, ICP-OES-inductively coupled plasma emission spectrometer was used for quantitative analysis of Li element, and according to GB / T9723-2007 chemical reagents and flame atomic absorption spectrometry general rules, AAS-atomic absorption spectrophotometer was used for quantitative analysis of A element. In the element quantitative analysis test results in Table 1,
[0074] Li x A y In C2O4:
[0075] Li mass percentage = total mass of Li / total mass of (Li+A);
[0076] A mass percentage = A total mass / (Li + A) total mass;
[0077] The conversion calculation can obtain x and y respectively.
[0078] Table 1 shows the 8 different Li x A y Quantitative element analysis of C2O4. According to the mass ratio of Li and A, the corresponding molar ratio can be calculated to calculate Li x A y The x and y values in C2O4.
[0079] Table 1
[0080]
[0081] Li x A y C2O4 material decomposition performance test
[0082] First lithium removal specific capacity (mAh / g) = first lithium removal capacity / mass of active material
[0083] Theoretical first lithium removal capacity (mAh / g) = theoretical total Li removal capacity / mass of active material
[0084] Among them, the first lithium removal specific capacity measured by S1-S8 reflects the Li x A y The delithiation specific capacity of C2O4 material. The test method of the first delithiation specific capacity is: in the blue battery test cabinet, the battery sample is charged at a charging current density of 0.1C to a cut-off voltage of 4.6V or 4.8V, and then the operation is stopped to obtain the first delithiation specific capacity.
[0085] The calculation method of the theoretical total Li removal capacity (corresponding to the theoretical first lithium removal specific capacity) is as follows:
[0086] (1) 1 mol of Li x A y C2O4 material can remove lithium xmol;
[0087] (2) The charge of x mol of Li = x mol*6.02*10 23 mol -1 *1.602*10 -19 C=x mol*6.02*10 23 mol -1 *1.602*10 -19 A·S=xmol*6.02*10 23 mol -1 *1.602*10 -19*(1000 / 3600)mAh, get the power in mAh;
[0088] (3) The power in mAh calculated in step (2) is divided by Li x A y The mass of C2O4 in g is used to obtain the theoretical first delithiation specific capacity, and the unit of the theoretical first delithiation specific capacity is mAh / g.
[0089] The test method for the first charging voltage platform is: using constant current charging in a blue battery test cabinet, charging the battery sample at a charging current density of 0.1C to a cut-off voltage of 4.6V or 4.8V and then stopping the operation to obtain a charging voltage-specific capacity curve (first charge and discharge curve). The platform of the charging voltage-specific capacity curve corresponds to the first charging voltage platform of the battery.
[0090] Examples 1-8 are all based on Li x A y C2O4 material is used as the main body of the battery positive electrode, the purpose is to more intuitively and simply test Li x A y The delithiation potential of C2O4 material (corresponding to the first charging voltage platform measured by the battery samples of Examples 1-8) and the delithiation specific capacity (corresponding to the first delithiation specific capacity measured by the battery samples of Examples 1-8) are as follows: x A y The verification of C2O4 as a battery positive electrode additive is in the next part of the lithium replenishment performance test.
[0091] In Examples 1-8, the main material of the positive electrode of the battery is Li x A y C2O4, during the first charge, Li x A y C2O4 begins to decompose and release active lithium at a certain voltage platform. x A y The decomposition performance of C2O4 includes two aspects: one is the initial lithium removal capacity, and the other is the lithium removal potential. The initial lithium removal capacity of battery samples S1-S8 of Examples 1-8 reflects the Li x A y The active lithium capacity released by C2O4 after delithiation; the delithiation potential corresponds to Li x A y The potential required for C2O4 to decompose and release active lithium reacts with Li x A y The ease of decomposition of C2O4 to release lithium is reflected by the first charging voltage platform of battery samples S1-S8 in Examples 1-8. When the lithium removal potential is reached, Li x A yC2O4 decomposes and releases lithium ions. The lower the delithiation potential and the higher the delithiation specific capacity, the higher the Li x A y The lithium replenishment performance is better when C2O4 is used as a positive electrode additive.
[0092] (1) Same as K + Cations, Li with different Li ratios x A y Comparison of C2O4 decomposition performance
[0093] Figure 1 The charge and discharge curves of battery samples S3, S4, S5 and DS1 at a charge and discharge rate of 0.1 C. The test results of the first delithiation specific capacity and the first charging voltage platform of Examples 1-5 and Comparative Example DS1 are shown in Table 2. It can be found that the theoretical first lithium desorption capacity increases with the increase of Li content, and the theoretical value is higher. This is because the partially substituted K does not participate in the decomposition and release, and will not contribute to the capacity. Comparing the theoretical and actual first lithium desorption capacity, S1, S2, S3, S4 and S5 are all completely delithiated at 4.6V, releasing the theoretical amount of active lithium, while DS1 is Li2C2O4 without A cation doping, and the actual first lithium desorption capacity at a cut-off voltage of 4.8V is only 64.6% of the theoretical value, and Li is not completely desorbed. Comparing the first charging voltage platform, that is, the Li desorption platform potential (delithiation potential), the higher the Li content, the less A cation doping, and the higher the delithiation potential, DS1-4.7V>S5-4.55V>S4-4.51V>S3-4.47V>S2-4.23V>S1-4.11V. Therefore, Li x A y When part of the Li in C2O4 material is replaced by K, its delithiation potential decreases.
[0094] Table 2
[0095]
[0096] Figure 1 The test results in Table 2 show that the delithiation potential of the DS1 sample is 4.7 V. When the charge cutoff potential is set at 4.6 V, the DS1 sample does not decompose, and the first delithiation specific capacity is about zero. In the battery system with a cutoff potential of 4.6 V, the S1, S2, S3, S4 and S5 samples have higher first delithiation specific capacities than the DS1 sample, indicating that the Li x A y C2O4 can provide more active lithium to the negative electrode than Li2C2O4. At the same time, S1, S2, S3, S4 and S5 samples have a lower first charge voltage platform than DS1, indicating that Li x A yWhen C2O4 is used as a positive electrode additive material, it can decompose and release active lithium under lower voltage conditions, which can avoid the influence of high charging voltage on the structure of positive electrode active materials and improve the stability and cycle performance of the battery.
[0097] When Li x A y When C2O4 is used as a positive electrode additive material to replenish lithium in the negative electrode, the maximum charge cut-off voltage that the battery system can withstand can be comprehensively considered. x A y The lithium desorption potential and lithium desorption specific capacity of C2O4 can obtain the maximum lithium replenishment capacity without affecting the battery system.
[0098] (2) Same Li ratio, different K + and Na + Li x A y Comparison of decomposition performance of C2O4 materials
[0099] Figure 2 The charge and discharge curves of battery samples S4 and S6 at a charge and discharge rate of 0.1C are shown in Table 3. The test results of the first delithiation capacity and the first charging voltage platform are shown in Table 3. It can be found that the theoretical first delithiation capacity has a small difference when the Li ratio is the same, and only a small amount of doped A ions K and Na have different relative atomic masses, which are basically consistent; comparing the theoretical and actual first delithiation capacity, S4 and S6 are completely delithiated at 4.6V, releasing the theoretical amount of active lithium; comparing the first charging voltage platform, that is, the delithiation potential, it shows that S6-4.54V>S4-4.51V, resulting in the difference in delithiation potential mainly related to the ionic radius of the doped cations, which are S4-K and S6-K respectively. + -133pm>S6-Na + -97pm, the larger the ion radius, the more lattice distortion it causes, resulting in a larger interlayer distance, and a larger distance between Li and anions, which in turn makes the interaction between Li and anions weaker, making it easier for Li to be released during charging, and the lower the lithium removal potential (first charge voltage platform). x A y When part of the Li in C2O4 material is replaced by A, its delithiation potential is reduced and the actual available active lithium capacity is improved.
[0100] As shown in Table 3, K + and Na + Co-doped Li x A y The C2O4 material completely delithiates at 4.6V, releasing the theoretical amount of active lithium. The first charging voltage platform, i.e., the delithiation potential, shows S7-4.52V, which is between S4 and S6. This performance is also related to the ionic radius.+ Co-doping can also reduce Li x A y The delithiation potential of C2O4 material is improved, and the actual available active lithium capacity is increased.
[0101] Table 3
[0102]
[0103] (3) Li with different particle sizes 1.94 K 0.06 Comparison of decomposition performance of C2O4 materials
[0104] Li particles of different sizes 1.94 K 0.06 The decomposition performance of C2O4 materials (first delithiation capacity and first charging voltage platform) is shown in Table 4. Comparing the theoretical and actual first delithiation capacity, S4 and S8 are completely delithiated at 4.6V, releasing the theoretical amount of active lithium; comparing the first charging voltage platform, i.e., delithiation potential, it shows that S7-4.57V>S4-4.51V, resulting in the difference in delithiation potential mainly due to Li 1.94 K 0.06 It is related to the particle size of C2O4 material. S4 is a particle with an average particle size of 300nm, while S8 is a large particle with an average particle size of 1μm. The smaller the particle size, the better the electrical contact with the conductive agent, electrolyte, etc., the smaller the battery polarization will be, and the corresponding delithiation potential will be lower. The larger the particle size, the greater the battery polarization will be, resulting in a higher delithiation potential.
[0105] Table 4
[0106]
[0107] 3. Li x A y Lithium replenishment performance test of C2O4 material
[0108] Examples 9-13 are Li x A y C2O4 material is introduced into the lithium iron phosphate battery system as a positive electrode additive material, and the quality of the positive electrode materials described in S9-S12 and DS2 is the same. The LiFePO4 and Li in S13 1.94 K 0.06 The total mass of C2O4 is the same as the mass of the positive electrode material described in S9-S12. x A y The lithium replenishment effect of C2O4 material, the active lithium released by its decomposition can be used to make up for the active lithium consumed by the negative electrode SEI, thereby increasing the battery capacity.
[0109] The charge and discharge regime of batteries S9-13 and DS2 is a charge cut-off voltage of 4.6V and a discharge cut-off voltage of 2.00V. The first charge and discharge capacities of batteries S9-13 and DS2 are listed in Table 5. The results show that the positive electrode active material LiFePO4 of the DS2 battery has a capacity of 1082.1mAh in the first charge, and the negative electrode SEI generation consumes about 12% of the active lithium, so that only 952.2mAh can be embedded in the first discharge; while the positive electrode of S9-13 introduces the additive Li x A y C2O4 decomposes to provide active lithium during the charging process. The battery discharge capacity is basically the same as the charging capacity of DS2, indicating that Li x A y The active lithium provided by the decomposition of C2O4 during the charging process can meet the consumption of SEI film, replenish sufficient active lithium, and enable sufficient active lithium to be discharged and embedded back into LiFePO4. x A y C2O4 material can replenish the active lithium consumed by the negative electrode SEI film, thereby significantly improving the capacity of the battery.
[0110] Table 5
[0111] Battery ID First charge capacity mAh First discharge capacity mAh S9 1194.3 1069.1 S10 1239.9 1069.6 S11 1290.3 1075.3 S12 1309.2 1073.7 S13 1291.7 1077.1 DS2 1082.1 952.2
Claims
1. A positive electrode additive for lithium ion batteries, characterized in that: The positive electrode additive of the lithium ion battery is Li x A y C2O4, A is selected from at least one of K+ and Na+, x+y=2, 1<x<2; The Li x A y The average particle size of C2O4 is 50nm~10μm.
2. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y In C2O4, 1.5≤x<2.
3. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y In C2O4, 1.9≤x<2.
4. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y The delithiation potential of C2O4 is no higher than 4.6V.
5. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y The delithiation potential of C2O4 is 4.1V~4.6V.
6. The lithium ion battery positive electrode additive according to claim 1, characterized in that: The Li x A y The average particle size of C2O4 is 100nm~1μm.
7. A positive electrode plate for a lithium-ion battery, characterized in that: The positive electrode sheet of the lithium ion battery comprises claims 1 to The lithium-ion battery positive electrode additive according to any one of 6.
8. The positive electrode sheet of a lithium-ion battery according to claim 7, characterized in that: The positive electrode plate of the lithium-ion battery comprises a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer satisfies the following conditions (1) or (2): (1) The positive electrode material layer comprises the lithium ion battery positive electrode additive and the positive electrode active material; (2) The positive electrode material layer includes a positive electrode active material layer and a positive electrode additive material layer disposed on the positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode additive material layer includes the lithium ion battery positive electrode additive.
9. The positive electrode sheet of a lithium-ion battery according to claim 7 or 8, characterized in that: The lithium-ion battery positive electrode plate includes a positive electrode active material, and the positive electrode active material is selected from at least one of LiFePO4, LiMn2O4 and nickel-cobalt-manganese ternary materials; in the lithium-ion battery positive electrode plate, the mass ratio r of the lithium-ion battery positive electrode additive to the positive electrode active material satisfies 0<r≤0.
15.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet according to any one of claims 7 to 9.
Citation Information
Patent Citations
Lithium-doped modified high-nickel low-cobalt ternary positive electrode material for lithium ion battery, and preparation method thereof
CN112768687A
Lithium ion battery positive electrode slurry and lithium ion battery
CN113839007A
Positive electrode lithium supplement agent and preparation method and application thereof
CN117936787A
Bulk phase doping modified lithium oxalate lithium supplement material and preparation method and application thereof
CN118336157A